Avelumab (anti-PD-L1) in platinum-resistant/refractory ovarian cancer: JAVELIN Ovarian 200 Phase III study design - Éric Pujade-Lauraine; Keiichi Fujiwara; Samuel S. Dychter; Geeta Devgan; Bradley J. Monk (2018)
Avelumab is a human anti-PD-L1 checkpoint inhibitor with clinical activity in multiple solid tumors. Here, we describe the rationale and design for JAVELIN Ovarian 200 (NCT02580058), the first randomized Phase III trial to evaluate the role of checkpoint inhibition in women with ovarian cancer. This three-arm trial is comparing avelumab administered alone or in combination with pegylated liposomal doxorubicin versus pegylated liposomal doxorubicin alone in patients with platinum-resistant/refractory recurrent ovarian, fallopian tube or peritoneal cancer. Eligible patients are not preselected based on PD-L1 expression and may have received up to three prior lines of chemotherapy for platinum-sensitive disease, but none for resistant disease. Overall survival and progression-free survival are primary end points, and secondary end points include biomarker evaluations and pharmacokinetics.